Rancang Bangun Media Pembelajaran Pengantar TI Metode Game Development Life Cycle - Putri, Ni Nyoman Juliani; Paramitha, A.A. Istri Ita; Anggara, I Nyoman Yudi (STIKOM Tunas Bangsa Pematangsiantar, 2024)
At the Faculty of Information Technology and Design, especially the Information Systems and Accounting Information Systems study program at Primakara University, there is a need to present learning media as an example of applying multimedia in the Introduction to Information Technology course. To meet these needs, this research aims to develop a game as an example of the application of interactive multimedia. In the development process, researchers utilized the Game Development Life Cycle method. This development has stages of initiation, pre-production, production, testing, beta and release. Testing of game development results is carried out using the ISO 9126-1 model, with limited aspects of functionality, usability and portability testing as well as media expert testing. The testing will involve students from the class of 2023 who have taken introductory information technology courses. Apart from that, learning media assessments were also carried out by media experts. From testing the interactive multimedia learning media